The Impact of Sustainable Marketing on Market Share in the Banking Industry in Southeast Asia: Moderating Role of Corporate Social Responsibility (CSR) - Utami, Septi Melia (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Market share is a crucial indicator reflecting a company's competitive position, especially in the highly dynamic banking sector. In the modern era, the urgency of sustainability has influenced consumer preferences, compelling companies, including the banking industry in Southeast Asia, to integrate sustainable marketing principles into their business and marketing strategies. This study examines the impact of sustainable marketing on market share in the Southeast Asian banking industry, with Corporate Social Responsibility (CSR) as a moderating variable. The research focuses on three dimensions of sustainable marketing: environmental, social, and economic dimensions, measured through environmental innovation score, product responsibility score, and product access low price score respectively. Using panel data from 26 banks listed in Refinitiv database during 2019-2023, this study employs Fixed Effects Model regression analysis to test seven hypotheses and Eviews as a data processing tool. The findings reveal that environmental and social dimensions of sustainable marketing, as well as CSR, have positive and significant effects on market share. However, the economic dimension of sustainable marketing shows no significant impact on market share. Regarding moderation effects, CSR does not significantly moderate the relationship between any dimensions of sustainable marketing and market share. The study contributes to sustainable marketing literature by providing empirical evidence from the banking sector in Southeast Asia. The results suggest that banks should prioritize environmental innovation and product responsibility initiatives while maintaining strong CSR strategies to enhance their market position, even though CSR's moderating role was not statistically confirmed at the 5% significance level